A study of the effects of the cathode configuration on the plasma kinetics and neutron emission of plasma-focus discharges in deuterium - Barbaglia, Mario Oscar; Giovachini, Ricardo Hernán; Milanese, Maria Magdalena; Clausse, Alejandro (IOP Publishing, 2020)
Fil: Barbaglia, Mario Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina